When Carry Fades : Maturity-Driven Decline in Currency Carry Trade Returns - Rämä, Totti (My University, 2026)
This bachelor's thesis examines why carry trade strategies are not fundamentally profitable in long-term investment approaches, particularly when implemented as a buy-and-hold strategy. The analysis is confined explicitly to currency carry trades, which represent the most widely recognized form of carry strategy. In conventional carry trade implementations, investors borrow in a low-interest-rate currency and subsequently invest the proceeds in higher-yielding financial instruments. Within this framework, the carry component is derived from the interest rate differential between the two countries involved. According to the uncovered interest parity theory, exchange rate movements should offset any interest rate differentials, rendering carry trade investments unprofitable. However, extensive empirical research has consistently demonstrated that this theoretical prediction fails to hold in practice. This persistent deviation from theory has historically provided investors with substantial excess returns spanning multiple decades. An investor's returns from carry trades emerge from three distinct components: exchange rate fluctuations, interest rate changes in both the funding and investment countries, and the re-turns generated by the selected financial instrument. Currency carry trades have received considerable scholarly attention over recent decades due to their complex risk profile and fundamental importance to international financial markets. These strategies exert a significant influence on financial market stability, particularly given that carry trade positions are typically ac-cumulated during low-interest-rate environments and frequently financed through substantial leverage. Carry trade investments are inherently vulnerable to abrupt unwinding events, driven by their pronounced negative skewness in return distributions. Carry trade unwinding can precipitate substantial turbulence across international financial markets. This thesis adopts a literature review methodology. The analysis focuses on the most prevalent fixed-income instruments. The thesis seeks to identify positive correlations between currency and fixed-income markets that investors might exploit to generate positive risk-adjusted re-turns. Consequently, the examination reflects an asset management perspective. The thesis provides compelling evidence against long-maturity carry trade investments. As investment maturity lengthens, uncovered interest parity holds proportionally. Conversely, short-term carry trade investments remain profitable, as deviations from the theory occur far more frequently over shorter time horizons.

Tämän kandidaatintutkielman tarkoituksena on selvittää, miksi carry trade -strategia ei lähtö-kohtaisesti sovellu pitkän tähtäimen sijoitusstrategiaksi, etenkään osta ja pidä -strategiaksi. Tutkielman on rajattu käsittämään valuuttoihin perustuvaa carry trade -strategiaa. Tämä on tunnetuin carry traden muoto. Perinteisissä carry trade -strategioissa lainataan matalan korko-tason valuuttaa, minkä jälkeen lainattu raha sijoitetaan korkeamman tuoton sijoitusinstrumentteihin. Strategiassa carry-komponentti on maiden välinen korkoero. Kattamattoman korkopariteetti -teorian mukaan valuuttakurssien tulisi tasoittaa mahdolliset korkoerot tehden carry trade -sijoituksista kannattamattomia. Lukuisat tutkimukset kuitenkin osoittavat, että teoria ei pidä käytännössä paikkaansa. Tämän talousteorian paikkansapitämättömyys on tarjonnut sijoittajille positiivisia ylituottoja vuosikymmenien ajan. Sijoittajan tuotto muodostuu kolmesta eri komponentista: valuuttakurssien muutoksista, korkotason muutoksista sekä lähtö- että kohdemaassa ja valitun sijoitusinstrumentin tuotosta. Carry trade -strategiaa on tutkittu laajasti viime vuosikymmeninä sen monimutkaisen riskiprofiilin ja keskeisen merkityksen vuoksi kansainvälisillä rahoitusmarkkinoilla. Strategialla on merkittävä vaikutus rahoitusmarkkinoiden vakauteen, sillä carry trade -sijoituksia on lisätty matalan korkotason vallitessa, ja ne ovat usein rahoitettu suurilla velkavivuilla. Carry trade sijoitukset ovat alttiita äkillisille purkautumisille niiden voimakkaan negatiivisesti vinoutuneen tuottojakauman vuoksi. Carry traden purkautuminen voi aiheuttaa voimakasta epävarmuutta kansainvälisillä rahoitusmarkkinoilla. Tutkielma on laadittu kirjallisuuskatsauksena. Mahdollisiksi sijoitusinstrumenteiksi on rajattu tyypillisimmät korkoinstrumentit. Tutkielma pyrkii löytämään positiivisia korrelaatioihin valuutta- ja korkomarkkinoiden välillä, joista sijoittaja voisi hyötyä. Täten tarkastelu edustaa erityisesti varainhoidon näkökulmaa. Tutkielma osoittaa voimakasta näyttöä pitkän maturiteetin carry trade -sijoituksia vastaan. Kun maturiteettia pidennetään, kattamaton korkopariteetti -teoria pitää voimakkaammin paikkaansa. Lyhyen aikavälin carry trade -sijoitukset kuitenkin ovat kannattavia, sillä teoria poikkeamia teoriasta esiintyy huomattavasti enemmän lyhyellä aikavälillä.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|; Rahoitus